1970
DOI: 10.1039/tf9706601648
|View full text |Cite
|
Sign up to set email alerts
|

Ionization measurements and absolute radiation yields in the ?-radiolysis of gaseous hydrogen sulphide

Abstract: Ion currents produced in hydrogen sulphide in a cylindrical ion chamber by y-radiolysis have been measured. Saturation points on the ion current curves were located by application of general recombination theory. These saturation currents were then used to estimate that the average energy W(H2S) required to produce an ion pair in hydrogen sulphide is 25.3f0.4 eV. Other values determined were W(CH3SH) = 25.1 f0.4 eV, W(N20) = 32.7f0.4 eV and W(SFs) = 35.0f0.4 eV. Hydrogen and sulphur are produced upon irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1971
1971
1976
1976

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…of these authors in that SF, reduces the hydrogen6 -yield. The decrease we observe is in good agreethe value of W = 25.3 eV per ion pair(8). ThisMOLE PERCENT SF6value of W measured by Huyton and Woodward FIG.2.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…of these authors in that SF, reduces the hydrogen6 -yield. The decrease we observe is in good agreethe value of W = 25.3 eV per ion pair(8). ThisMOLE PERCENT SF6value of W measured by Huyton and Woodward FIG.2.…”
supporting
confidence: 89%
“…They also reported that this yield is reduced by the addition of SF,, although they did not state by how much. Huyton and Woodward (7,8) y-irradiated gaseous H2S and measured the dose by ion chamber measurements. They report G(H2) = 7.0 _+ 0.2 at 800 Torr and that neither N 2 0 nor SF, has any effect on this yield (7).…”
Section: Introductionmentioning
confidence: 99%
“…Rcently several studies of the radiolysis of hydrogen sulfide have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and we have proposed a mechanism based on our measurements at high dose rates (13). While this mechanism is in general agreement with the observed yields there are problems which need further investigation.…”
Section: Introductionsupporting
confidence: 77%
“…It requires an accurate value of W, the average amount of energy expended in the gas per ion pair formed. The reproducibility of W values from one laboratory to the next is within about 4% (570050,580061,640177,650795,670437,680390,680843,680844,700510,710122).…”
Section: Gas Phasementioning
confidence: 87%